2000
DOI: 10.1002/1096-9896(2000)9999:9999<::aid-path690>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic evaluation of virus‐associated and non‐viral hepatocellular carcinoma: analysis of 26 carcinomas and 12 concurrent dysplasias

Abstract: The worldwide incidence of hepatocellular carcinoma (HCC) is approximately one million cases a year. This makes HCC one of the most frequent human malignancies, especially in Asia and Africa, although the incidence is increasing also in the western world. HCC is a complication of chronic liver disease, with cirrhosis as the most important risk factor. Viral co-pathogenesis makes cirrhosis due to hepatitis B (HBV) and hepatitis C virus (HCV) infection a very important factor in the development of HCC. As curati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(67 citation statements)
references
References 36 publications
2
65
0
Order By: Relevance
“…The multiple hepatocarcinogenesis involves large molecular events including genetic and epigenetic changes, which accumulate through progression (Hui and Makuuchi, 1999;Zimmermann et al, 1997). The genetic deviation encompasses DNA rearrangements associated with viral genome integration (Zondervan et al, 2000), point mutations (Ogata et al, 1991;Shimizu et al, 1999;de La Coste et al, 1998), loss of heterozygosity (Teeguarden et al, 2000;Kondo et al, 2000), chromosomal amplifications (Kawate et al, 1999), changes in methylation (Kondo et al, 2000;Shen et al, 1998), translocations (Keck et al, 1999), and gain or loss of imprinting (de Souza et al, 1997;Schwienbacher et al, 2000). These changes could occur in a variety of cellular genes leading to escape from normal cellular and environmental controls.…”
Section: Introductionmentioning
confidence: 98%
“…The multiple hepatocarcinogenesis involves large molecular events including genetic and epigenetic changes, which accumulate through progression (Hui and Makuuchi, 1999;Zimmermann et al, 1997). The genetic deviation encompasses DNA rearrangements associated with viral genome integration (Zondervan et al, 2000), point mutations (Ogata et al, 1991;Shimizu et al, 1999;de La Coste et al, 1998), loss of heterozygosity (Teeguarden et al, 2000;Kondo et al, 2000), chromosomal amplifications (Kawate et al, 1999), changes in methylation (Kondo et al, 2000;Shen et al, 1998), translocations (Keck et al, 1999), and gain or loss of imprinting (de Souza et al, 1997;Schwienbacher et al, 2000). These changes could occur in a variety of cellular genes leading to escape from normal cellular and environmental controls.…”
Section: Introductionmentioning
confidence: 98%
“…For example, deleted in liver cancer 1 (DLC1) on 8p21-p22, 7 E-cadherin (CDH1) on 16q12.1-q23.1 8 and tumor protein p53 (TP53) on 17p13. 9 Candidate genes in the smallest overlapping regions 4q12-q23 10 and 4q31-q35, on the other hands, remains undescribed. 11,12 As regions of aberrant genomic loci can harbor more than one tumor-related genes, such as RASSF1A, MLH1, TGFBR2 and BLU on chromosome 3p21, [13][14][15][16] the existence of more than one tumor-suppressor gene within common deleted sites of hepatocellular carcinoma cannot be ruled out.…”
mentioning
confidence: 99%
“…The site of the cellular DNA at which the HBV integrates frequently undergoes rearrangement, resulting in a translocation, and deletion (Ogata et al,1990;Hino et al, 1996;Nakamura et al, 1998;Okabe et al, 2000). Furthermore, an allelic loss at 13q is significantly associated with an advanced tumor stage and a poor prognosis (Zondervan et al, 2000;Kusano et al, 2002;Wong et al, 2002). Therefore, it is possible that an allelic loss of KCNRG could be an additional mechanism for the progression of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Several cytogenetic studies reported that chromosome 13q is one of the common deletion regions and contains one or more of the genes associated with the development or progression of HCC (Niketeghad et al, 2001;Crawley et al, 2002; Genetic and expression analysis of the KCNRG gene in hepatocellular carcinomas Kusano et al, 2002;Wong et al, 2002). Surprisingly, allelic losses at 13q were found to be associated with an advanced tumor stage and a poor prognosis (Zondervan et al, 2000;Kusano et al, 2002;Wong et al, 2002). The potassium channels are ubiquitous multisubunit membrane proteins that regulate the membrane potential in several cell types, and potassium-dependent alterations in the membrane potential play a pivotal role in the proliferation of many types of normal and tumor cell lines.…”
Section: Introductionmentioning
confidence: 99%